Political Party Pragmatism: The Emergence of Single Pair in Ngawi Regency Head Election - Prastya, Danang Eko; Purwaningsih, Titin; Qodir, Zuly (Jurnal Magister Administrasi Publik, 2021)
This study aims to determine the emergence of a single pair in the regional head election of Ngawi Regency in 2020. The research uses descriptive qualitative methods to describe the facts of existing symptoms or phenomena. Data collection is carried out by tracing scientific journals, government reports, regulations, mass media news, and other articles relevant to the emergence of a single candidate in the head of the local election. Data analysis was carried out by reducing, presenting data, and drawing conclusions. The study results show that the large coalition of political parties supporting the pair Ony Anwar Harsono and Dwi Rianto Jatmiko with the tagline "OK Win Together" has a pragmatic and victory-oriented tendency to gain power. This pair is supported by the majority of parties in the Ngawi Regency DPRD, with 45 seats. There are ten supporting political parties, including PDIP, Golkar, PKS, Gerindra, PKB, Nasdem, Democrat, Hanura, PAN, and PPP. This large and majority coalition's built-in support of the pair Ony Anwar Harsono and Dwi Rianto Jatmiko shows the tendency of the party to ignore its ideological platform and desire to win to present a single pair in the 2020 regional head election in Ngawi Regency